Smoking as a Risk Factor for Dry Socket: A Systematic Review - Weronika Kuśnierek; Kaja Brzezińska; Kacper Nijakowski; Anna Surdacka (MDPI AG, 2022)
Dry socket is one of the postoperative complications of tooth extraction. It is the partial or total loss of the post-extraction blood clot, resulting in severe pain that usually starts one to five days postoperatively, with clinical evidence of exposed alveolar bone, necrotic debris, halitosis, and tenderness on examination. The purpose of our systematic review was to answer the question "Is there a relationship between smoking and dry socket?". After meeting the inclusion and exclusion criteria, eleven studies were included in this systematic review (according to the PRISMA statement guidelines). Based on a meta-analysis, tobacco smokers had a more than three-fold increase in the odds of dry socket after tooth extraction. Overall, the combined incidence of dry socket in smokers was found to be about 13.2% and in non-smokers about 3.8%. Despite the heterogeneity of the included studies (different types of teeth extracted, different age groups), cigarette smoking was related to an increased risk of dry socket after tooth extraction.